Statistical Assessment of the Product Innovation Impact on Employment and Wages in Ukrainian Industry - Ishchuk, S. O.; Sozanskyy, L. Yo. (Statistics of Ukraine, 2023)
Innovation activity of industrial enterprises is one of the most important prerequisites for the socio-economic development of the country. Innovations contribute to the growth of labor productivity, value added and profit, and, consequently, to an increase in the level of wages. Studies of patterns of the product innovation impact (measured as an indicator of the share of innovative products in industrial sales) on employment and wages in the industrial sector of the economy has, therefore, significant theoretical and practical importance. The purpose of the article is a statistical assessment of the relationships between product innovation and employment, as well as between product innovation and wages in Ukrainian industry. Analytical confirmation of a significant decrease in the level of product innovation and employment in Ukrainian industry over the past decades is provided. Using correlation-regression analysis methods, it was empirically proven that there is a high positive correlation between the innovativeness of products and the share of industry in the employment structure of the Ukrainian economy. A regression model was built, allowing to determine how the employment in Ukrainian industry will change with changing the product innovativeness by 1 pp. Almon’s method was used to build a distribution-lag model (with a lag of three years) reflecting a high positive dependence of the index of average monthly salary of a full-time employee in the Ukrainian industry on the growth of the product innovation index. On the basis of proven regularities, a deterministic econometric model for optimization of the technological structure of realized industrial products and innovative products in the context of manufacturing industry was developed and tested at the level of Ukraine; the model was used in estimations by linear programming technique. The optimization criterion is a product innovation increase. The results of modeling lay a theoretical basis for strategic macroeconomic planning and socio-economic forecasting, as they allow for choosing a target optimization function at which wages in the manufacturing industry of Ukraine will reach the desired value. Innovative activity of industrial enterprises is one of the most important prerequisites for the socio-economic development of the country. Innovations contribute to the growth of labor productivity, added value and profit, and as a result, to an increase in the level of wages. Accordingly, the study of patterns of impact of product innovation (expressed as an indicator of the share of innovative products in the volume of industrial products sold) on employment and wages in the industrial sector of the economy has significant scientific and applied importance. The purpose of the article is a statistical assessment of the relationships between product innovation and employment, as well as between product innovation and wages in Ukrainian industry. Analytical confirmation of a significant decrease in the level of product innovation and employment in Ukrainian industry over the past decades. With the help of correlation-regression analysis methods, it has been empirically proven that there is a high direct relationship between the innovativeness of products and the share of industry in the structure of employment in the Ukrainian economy. A regression model has been built, with the help of which it is possible to determine how employment in Ukrainian industry will change when the innovativeness of products changes by 1 p.p. Using Almon’s method, a distribution-lag model (with a lag of three years) was built, which reflects the high direct dependence of the index of the average monthly salary of a full-time employee of the Ukrainian industry on the growth of the index of product innovation. On the basis of proven regularities, a deterministic economic-mathematical model for optimization of the technological structure of realized industrial products and innovative products in the context of production of the processing industry was developed and tested at the level of Ukraine, which was solved by the method of linear programming. The optimization criterion is the increase in product innovation. The results of modeling form a scientific basis for strategic macroeconomic planning and forecasting of socio-economic development, as they allow choosing such a target optimization function at which wages in the processing industry of Ukraine will reach the desired value.